Dirty Code for a Dirty City. - Jones, Nathan; Greenwood, Mark (Performance Research, 2013)
The article offers the insights of Nathan Jones and Mark Greenwood, co-creators of the Live Writing project, regarding their creation and production of an interface and code for the project. Topics discussed include a software that would allow a written poetry to intermix the visual language, accompanying animations with beats and rhythms, and the completion of the project's feedback loop.